(untitled) (Socio-economic relations in the digital society, 2019)
At present, Ukraine’s economy requires rapid structural and technological change, while improving cash settlement mechanism, as its current condition is characterized by disorder of payment and settlement systems and payment crisis. Timely and full payment for the received material assets, work performed and services rendered, other debt is one of the main prerequisites and signs the effi ciency of the economy as a whole and each of its separate entity. This article examines the types, forms and features cash payments businesses, their principles and interaction analyzed positive and negative traits varieties cash payments businesses. Deals with cash payments significant role in the life cycle of the enterprise and the need to establish eff ective and transparent fl ow of funds. Deals with the direction of the funds are listed and described the settlement principles and their application. The method of calculation of the cash businesses with its phased implementation.